Rede de apoio social dos cuidadores de familiares com doença crônica de uma comunidade remanescente de quilombos - Silveira, Celso Leonel (2011)
It is a qualitative research, fulfilled on a quilombos remaining rural community in the south region of Brazil. The goal was to know the social support network of caregivers of relatives with chronic condition of health of this community. The individuals of research were caregivers of relatives with chronic health condition. It was used as criteria for inclusion: be the caregiver with chronic condition of health person, possess some degree of kinship with the person cared for, be caregiver for at least six months and not more than five years. It was used the data Saturation criterion for definition of the number of participants, totaling 13 caregivers. The data collection occurred through semi structured interview, observation and documentary analysis. Data analysis was through content analysis. The ethical principles were respected, in order to protect the rights of the participants, with the formalization of participation through the enlightened and free Term of agreement. The standards of resolution nº 196/96 of the National Health Council governing the researches involving human subjects were respected. The categories from data analysis are described and discussed in four articles, which compose the essence of this work. The social network was composed by the family, by neighbors and friends, by groups of coexistence, by members of religious congregations and by health professionals. The social support in networks was classified as emotional, informational and instrumental. The emotional support was received by family and living groups. The popular informative support was received from experienced people in the community, those who had gone through similar situations, by members of religious congregations and the belief system of each caregiver, being the professional informative support provided by health professionals. The instrumental backing was provided especially by the family. Social support is understood as inherent to the social networks of caregivers that can be mobilized in times of need. Generally, the social support network is characterized for being extensive and structured, providing social support to caregivers. This support is important, both to the personal life of the caregiver, as in assistance of family care activities. It was noted that care to a family member is perceived as a collective commitment of this family. On the basis of reciprocity, the care happens because the person "deserves" to be cared for. In dispensing care to another family member, naturally expected the consideration at the moment of weakness. In this context, the care can be considered as the boon that circulates between the members of each family. It is therefore concluded that if makes relevant to nursing and healthcare team, knowing the social networks of users of health services, as well as social support circulating in social networks, in order to act effectively and in a coordinated way with the support networks, considering that this effort can help in the conduct of home care, improving the quality of life of the sick person as well the family caregiver.